The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ma11081454
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties Study of Fe-Mn-Si Shape Memory Alloys Welding Seam Formed by Laser Welding with Filler Powder

Abstract: To reduce the residual stress and improve the fatigue property of the laser weldment by using the stress self-accommodation characteristic of Fe-Mn-Si shape memory alloys (SMAs), a Fe15Mn5Si12Cr6Ni memory alloy welding seam was formed inside 304 stainless steel by laser welding with filler powder. The combination of the hole-drilling method and the ANSYS software was used to research the distribution law of residual stress inside the laser welding specimen. The fatigue strength of the laser welded specimens wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The memory mechanism of Fe-Mn-Si shape memory alloys originates from thermally or stress-induced γ ↔ ε martensite transformation and its inverse transformation [16]. Ju [17] found that the characteristic of stress self-accommodation of Fe-Mn-Si shape memory alloy can effectively reduce the residual stress generated by laser welding and has excellent mechanical properties. Xu [18] successfully prepared a Fe-Mn-Si(SMA) coating on the surface of 304 stainless steel, which has the characteristic of stress self-accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…The memory mechanism of Fe-Mn-Si shape memory alloys originates from thermally or stress-induced γ ↔ ε martensite transformation and its inverse transformation [16]. Ju [17] found that the characteristic of stress self-accommodation of Fe-Mn-Si shape memory alloy can effectively reduce the residual stress generated by laser welding and has excellent mechanical properties. Xu [18] successfully prepared a Fe-Mn-Si(SMA) coating on the surface of 304 stainless steel, which has the characteristic of stress self-accommodation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the problem of elemental evaporation loss is solved industrially by increasing the content of low-boiling-point elements in the wire or powder feedstock or appropriately reducing the laser power. However, after the filling material enters the molten pool, the distribution of the filling elements in the weld may also have some unevenness due to the convection and agitation of the molten pool, which will affect the performance of the welded joint [10,11].…”
Section: Introductionmentioning
confidence: 99%